How women make money : inspirational stories and practical advice from successful Canadian entrepreneurs - Watson, Julie V., 1943- (Toronto : Dundurn Group, 2004)
How Women Make Money is an inspiring collection of profiles, anecdotes, and practical advice and guides that will help women take control of their lives and attain their financial goals. Whether you are starting a new business, growing an established one, supplementing a pension, working for "extras" for the family, or striving to fulfill a lifelong dream, this book will nurture your entrepreneurial spirit and give you the tools you need to achieve success.
Includes bibliographical references (pages 218-219) and index.
Print version record.
Keywords: Businesswomen -- Canada; Women-owned business enterprises -- Canada; Entrepreneurship -- Canada; Femmes d'affaires -- Canada; Entreprises appartenant à des femmes -- Canada; Entrepreneuriat -- Canada; BUSINESS & ECONOMICS -- Entrepreneurship; Businesswomen; Entrepreneurship; Women-owned business enterprises; Canada; Electronic books; Electronic books